Targets and overwork: Neoliberalism and the maximisation of profitability from the workplace. (March 2022) - Telford, Luke; Briggs, Daniel
Drawing on 25 qualitative interviews, this paper attends to and critiques neoliberalism to demonstrate how management's enforcement of targets and the expectancy to overwork in various workplaces corrodes the relationship between managers and employees. First, the paper briefly charts how the shift from post-war Keynesian welfare state capitalism to neoliberalism in the global north placed renewed emphasis on maximising profitability, and what this meant for working methods and innovations that managers now use to make an organisation more efficient. This is often regarded as 'management practices'. It then connects management practices to the political economy and therefore sheds further empirical light on how management practices under neoliberalism impact adversely on workers, generating psychological distress, instability, pressure and a negative working environment. The paper closes with a discussion of how managers potentially perform an ideological function, directing workers' attention away from neoliberalism and cementing capitalist realism; the negative ideological belief that there is no alternative to the current political economy.